KARAKTERISTIK BITUMEN ASBUTON BUTIR UNTUK CAMPURAN BERASPAL PANAS - Furqon Affandi (Jurnal Jalan-Jembatan, 2008)
Indonesia has imported asphalt from other countries to meet the need for road construction and annual maintenance. Meanwhile in Buton Island, Southeast Sulawesi Province, there is natural asphalt known as asbuton that has been produced since 1926. Asbuton was produced in convensional granular asbuton with maximum granular size of 12.5 mm since 1987. In that case, pavement performance using convensional granular asbuton was unsatisfactory, its production was practically ceased in 1987. In the early 1990 granular asbuton has been reproduced in a smaller granular size, packed in the water proved plastic bagit was used either in the hot or cold asphalt mixes. This paper describes the laboratory research result on the properties of granular asbuton for hot mix in terms of the function of granular asbuton in the mixture. The failure of asphalt mix specimen with granular asbuton using Marshall test, the analysis of aggregate gradation resulted from granular asbuton addition in the mixture, material loosing by Cantabrian Method were also xamined. The experiments show that the bitumen in granular asbuton is difficult to separat e from its mineral so it cannot coat and bind the aggregates. The solubility experiment of granular asbuton using kerosene heated 90oC for one hour, only about 55% of bitumen was dissolved. Therefore, asbuton bitumen is functionally ineffective in asphalt mixture as petroleum bitumen. Consequently, it influences the performance of asphalt mix and pavements. It is proved that the bitumi nous mix failure using granular asbuton in marshall test was splitted into two parts. Considering the above result, asbuton extraction granular of asbuton should be developed and will be applied for achieving better performance of asphalt mix and for effective utilization of asbuton. Key Words : granular asbuton, bituminous mixes, Marshall test, extraction, stability